2012
DOI: 10.1007/s13758-011-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Stability Studies of Poly(2-methyl-2-oxazoline) and Poly(ethylene glycol) Brush Coatings

Abstract: Non-fouling surfaces that resist non-specific adsorption of proteins, bacteria, and higher organisms are of particular interest in diverse applications ranging from marine coatings to diagnostic devices and biomedical implants. Poly(ethylene glycol) (PEG) is the most frequently used polymer to impart surfaces with such non-fouling properties. Nevertheless, limitations in PEG stability have stimulated research on alternative polymers that are potentially more stable than PEG. Among them, we previously investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
209
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(217 citation statements)
references
References 69 publications
6
209
0
Order By: Relevance
“…This graft copolymer was used to form surface platforms on Nb 2 O 5 [114] to investigate the adhesion mechanism of Escherichia coli and in particular the influence of fimbriae expression. Expressing type 1 fimbriae bacteria adhered due to van der Waals forces and hydrophobic interactions.…”
Section: Grafting Onto Surfacesmentioning
confidence: 99%
“…This graft copolymer was used to form surface platforms on Nb 2 O 5 [114] to investigate the adhesion mechanism of Escherichia coli and in particular the influence of fimbriae expression. Expressing type 1 fimbriae bacteria adhered due to van der Waals forces and hydrophobic interactions.…”
Section: Grafting Onto Surfacesmentioning
confidence: 99%
“…27 Nonetheless, one can question if such surfaces are robust enough for the harsh hospital operating conditions, given the mechanical and chemical fragility of tethered polymer surface layers. [28][29][30][31] Alternatively, biocide-releasing coatings offer the advantage of embedding the bioactive element in a scaffold, which can be chosen, for example, for its mechanical and chemical stability. Therefore, the remaining challenge in this case is to control the release kinetics, which governs the duration and effectiveness of the antibacterial action.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, α = I -CH2-N(C=O)- , which results in α value of 0.33. We have previously found that this value is the optimum grafting density value for PLL-g-PMOXA brush as biopassive surface coating (Pidhatika et al, 2010, Pidhatika et al, 2012. Figure 5 shows the NMR spectrum of PLL-g-PMOXA-QAC and the assignment of peaks.…”
Section: Resultsmentioning
confidence: 88%
“…One of them is loss of biopassive function in case of long-term application. It is believed that PEG degrades by auto-oxidation due to the repetitive oxygen atom in its structure (Pidhatika et al, 2012, Chen et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation